The Bargaining Position of Women in Village Fund Management in Balee Inong - Zainal Putra4, T. Lembong Misbah5Masrizal1, Partini2, Ishak Hasan3, (Opción, 2019)
The aim of the study is to investigate the bargaining position of women in village fund management in Balee Inong. This study uses a type of field research with qualitative methods with the approach of contemporary feminist ethnography. As a result, 10 percent of village funds are allocated for women’s activities from 90 villages in Banda Aceh. This study concluded that the Balee Inong was involved in managing village funds both from the Regional Budget (APBD) and the State Budget (APBN) and other sources of funds managed by the village.